If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -4k = 54 Solving 2 + -4k = 54 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -4k = 54 + -2 Combine like terms: 2 + -2 = 0 0 + -4k = 54 + -2 -4k = 54 + -2 Combine like terms: 54 + -2 = 52 -4k = 52 Divide each side by '-4'. k = -13 Simplifying k = -13
| -4x+5=3x-16 | | 8r+45=175.40 | | (2x+5)=log(20) | | 12=4+n/2 | | x+10=-11 | | x^3+5x+8=0 | | -x-8=6 | | -4x+5=3x+16 | | 5(1/5+c)=2/2/3 | | 2/3*5/6*14 | | 3(x+2)-4x=-2(x-3) | | 11.5=y | | 2y+3(y-2)=8y-5(y+10) | | -27+4-5= | | 56+38x= | | (x)(x+1)=156 | | 43*17= | | 5+36-13=13 | | -2-6x=52 | | 13=5+36-13 | | 2*4+6= | | 16t^2-96t-96=0 | | 204=4-10n | | -29=11p/59 | | 5(4X+3)=175 | | .5x(2x+2)=110 | | 1/2/3+3n=4/5n+15 | | 3x+4=12+7x | | 2y-10=-18 | | 52=4a | | (x+1)(x+2)=30 | | 4x=6x+20 |